Patterns of polypoidal choroidal vasculopathy among a multiracial population in a Malaysian hospital - Nazima SA,; Hanisah AH,; Rona Asnida Nasaruddin,; Wong, HS; Amin Ahem,; Bastion, Mae-Lynn Catherine; Mushawiahti Mustapha,; Hazlita Mohd Isa, (Faculty of Medicine, Universiti Kebangsaan Malaysia, 2016)
Polypoidal choroidal vasculopathy (PCV) is a retinal disorder characterized by aneurismal polypoidal lesions in choroidal vasculature. PCV appears to preferentially affect pigmented individuals and is considerably high among Asians. Most reports on patterns of PCV around Asia are based on a homogenous race (e.g. Chinese, Japanese) and very few descriptions from a multiracial population like those seen in Malaysia. The present study aimed to describe the demographic features, clinical and investigative characteristics of PCV in a multiracial group at Universiti Kebangsaaan Malaysia Medical Centre (UKMMC). Ninety one eyes of 86 PCV patients, comprising of Chinese (65.1%), Malays (31.4%), Indians (2.3%) and Eurasian (1.2%) were retrospectively reviewed. All underwent complete ophthalmic examination and investigations. Mean patient age was 70.4 years with a male preponderance (59.3%), and mostly unilateral presentation (94.1%). The logMAR mean presenting visual acuity was 0.78 ± 0.64. Polypoidal vascular lesions were located generally within the macula area (86.8%), manifesting mainly as submacular hemorrhage (59.3%). Interestingly a number of eyes (43.9%) had associated drusen. Optical coherence tomography largely demonstrated exudative changes (75.9%) and almost all patients (97.7%) had loss of external limiting membrane (ELM) and IS/OS interface. On indocyanine green angiography, majority of eyes had multiple polyps (82.4%) with ‘cluster’ (58.2%) being the commonest configuration. In conclusion, although the patterns of PCV in UKMMC were mainly similar to other Asian patients, a number of our patients had associated drusen. This indicates that PCV in our population could be a variant of neovascular age related macular degeneration and not solely idiopathic in nature.